2021
DOI: 10.3390/children8060498
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Therapeutic Plasma Exchange (TPE) in Multisystem Inflammatory Syndrome in Children (MIS-C)

Abstract: Multisystemic inflammatory syndrome in children (MIS-C) is a new potentially life-threatening disease that is related to coronavirus disease 2019 (COVID-19). The aim of this study is to reveal the clinical and laboratory results of MIS-C and the role of therapeutic plasma exchange (TPE) in its treatment. Clinical, laboratory and radiological characteristics of the patients who were admitted to the pediatric ward and pediatric intensive care unit (PICU) of a tertiary hospital with a diagnosis of MIS-C between A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…13 The mainstays in the therapy for PIMS are immunomodulation (glucocorticoids, immunoglobulins, Anakinra) and anticoagulant therapy. 14,15 In severe cases of suspected EVALI, the principles of treatment are similar.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…13 The mainstays in the therapy for PIMS are immunomodulation (glucocorticoids, immunoglobulins, Anakinra) and anticoagulant therapy. 14,15 In severe cases of suspected EVALI, the principles of treatment are similar.…”
Section: Discussionmentioning
confidence: 99%
“…21 TPE has also been successfully used for the treatment of inflammatory syndromes after SARS-CoV-2-infections in adults and children. 14,22 As a result, many authors consider TPE to be the last therapeutic resort when standard (immunomodulatory) therapy fails. The use of TPE in EVALI has not been reported to our knowledge and more study is certainly necessary.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Atay et al investigated the role of therapeutic plasma exchange in multisystem inflammatory syndrome in 41 children [ 22 ]. They concluded that therapeutic plasma exchange may be effective in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%